Bacterial Consortium Improves Sweet Corn Yield, Stover and Soil: Bacterial Consortium Improves Sweet Corn Yield, Stover and Soil - Purwanti, Eny Wahyuning; Sa’diyyah, Iqomatus; Navitasari, Lisa; Waskito, Heru (Journal of Tropical Life Science, 2026)
Plant growth–promoting rhizobacteria (PGPR) are promising bio-stimulants for sustainable agriculture, enhancing crop growth, nutrient use efficiency, and soil fertility while reducing dependence on chemical fertilizers. This study evaluated an indigenous consortium of Azotobacter vinelandii and Bacillus cereus on sweet corn (Zea mays L. var. saccharata). The study utilized a completely randomized design with three treatments: control (no PGPR), seed soaking and root drenching, each replicated five times. Growth parameters, yield, kernel quality, stover nutritive value, and soil fertility indicators were measured. Both PGPR application methods significantly improved plant growth and yield. Specifically, there was a marked increase in plant height, stem diameter, cob weight, and kernel sweetness (measured in °Brix). Furthermore, the quality of the stover used as animal feed substantially increased, characterized by higher crude protein, dry matter, and total digestible nutrients (TDN), while crude fiber, fat, and ash remained stable. The bacterial consortium successfully enhanced soil health and fertility indicators, including microbial populations, organic carbon content, and available phosphorus. Seed soaking consistently produced superior results compared to root drenching. The indigenous PGPR consortium proved highly effective as a sustainable bio-stimulant, capable of boosting sweet corn productivity, improving stover feed value, and promoting soil health. Farmers are advised to apply the consortium via seed soaking to maximize yield and quality while reducing fertilizer dependency, supporting sustainable crop–livestock’s integration.